Anaerobic Fungi: Past, Present, and Future - Hess, Matthias; Paul, Shyam S.; Puniya, Anil K.; van der Giezen, Mark; Shaw, Claire; Edwards, Joan E.; Fliegerová, Kateřina (Frontiers in Microbiology, 2020)
Anaerobic fungi (AF) play an essential role in feed conversion due to their potent fiber degrading enzymes and invasive growth. Much has been learned about this unusual fungal phylum since the paradigm shifting work of Colin Orpin in the 1970s, when he characterized the first AF. Molecular approaches targeting specific phylogenetic marker genes have facilitated taxonomic classification of AF, which had been previously been complicated by the complex life cycles and morphologies associated with different stages. Although we now have a much better understanding of their diversity, it is believed that there are still several not yet described genera of AF in the gut ecosystem. Recent marker-gene based studies have shown that fungal diversity in the herbivore gut is, much like the bacterial population, driven by host genetics as well as by diet. Since AF are major contributors to the degradation of plant material ingested by the host animal, it is understandable that there has been great interest in exploring the enzymatic repertoire of these microorganisms in order to establish a better understanding of how AF, and their enzymes, can be used to improve host health and performance, while simultaneously reducing the ecological footprint of the livestock industry. A detailed understanding of AF and their interaction with other gut microbes as well as the host animal is essential when one takes into consideration that livestock production will have to become significantly more efficient in order to provide affordable high-quality protein and other animal-based products for a global population that is predicted to reach ~10 billion by 2050. Such a mechanistic understanding, leading to more sustainable livestock practices, will be possible with recently developed omics technologies that have already provided first insights into the different contributions of the fungal and bacterial population in the rumen during plant cell wall hydrolysis. In this review, we discuss anaerobic fungi in term of current knowledge of their biology and ecology in the context of animal livestock production, and their future potential to accurately and reliably modify the digestive microbiome to support healthier and more productive animals whilst decreasing the environmental footprint of livestock production.